Dynamic analysis of physiological indices and transcriptome profiling revealing the mechanisms of the allelopathic effects of phenolic acids on Pinellia ternata - He, Zhigui; Wang, Yanfeng; Yan, Yan; Qin, Shaowei; He, Huan; Mao, Renjun; Liang, Zongsuo (Frontiers in Plant Science, 2022)
Pinellia ternata (Thunb.) is a famous traditional Chinese medicine with high medicinal value, but its culture is strongly hindered by the continuous cropping obstacles (CCOs) which are tightly associated with allelopathic effects. Deciphering the response mechanisms of P. ternata to allelochemicals is critical for overcoming the CCO. Here, we elucidate the response of P. ternata to phenolic acids treatment via physiological indices, cellular approaches, and transcriptome analysis. Phenolic acids showed a significant effect on the growth of P. ternata seedlings, similar to the phenotype of continuous cropping. Cellular analyses demonstrated that phenolic acids remarkably induced root cell death. Physiological analyses revealed that phenolic acids induced the over-accumulated of H2O2 and O2·− in root cells. However, two exogenous antioxidants (L-ascorbic acid and β-gentiobiose) aid in the scavenging of over-accumulated H2O2 and O2·− by promoting the antioxidant enzyme activity such as superoxide dismutase, peroxidase, and ascorbate peroxidase. Transcriptome analyses demonstrated that differentially expressed genes (DEGs) related to the cell wall degeneration and reactive oxygen species (ROS) metabolism were upregulated with phenolic acid treatment. In addition, downregulated DEGs involved in sucrose and starch metabolism and phenylpropanoid biosynthesis pathways decreased the key metabolites contents. Taken together, phenolic acids caused root cell death by inducing the overaccumulation of H2O2 and O2·− , and L-ascorbic acid and β-gentiobiose effectively alleviated ROS stress. The present study elucidates the underlying mechanism of the allelopathic effect of phenolic acids, offers valuable information for further understanding the mechanism of CCO, and could contribute to improving guidance for further P. ternata production.